2007
DOI: 10.1248/bpb.30.213
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structure-Dependent Differential Effects of Flavonoids on the Catalase Activity as Evaluated by a Chemiluminescent Method

Abstract: The antioxidative activity of flavonoids depends upon a combination of many factors, such as the concentration and chemical structure of the flavonoids and the arrangement of functional groups in their structure. In the present study, to evaluate the antioxidative effect of several types of flavonoids on catalase activity at a physiological H 2 O 2 concentration, a chemiluminescent (CL) method was used. The H 2 O 2 /luminol-dependent CL intensity in a system containing 3.7 nM catalase and low concentrations (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 32 publications
3
28
0
1
Order By: Relevance
“…Others have observed no effect or even a decrease of catalase expression and activity in cells after flavonoid treatment/digestion [22,23]. Only few works concerning flavonoid-catalase interaction in model systems have been published so far [24,25]. In the work of Doronicheva et al [24] catalase activity in the presence of flavonoids has been measured using chemiluminescence method in which hypochlorous acid has been used to oxidize luminol.…”
Section: Introductionmentioning
confidence: 99%
“…Others have observed no effect or even a decrease of catalase expression and activity in cells after flavonoid treatment/digestion [22,23]. Only few works concerning flavonoid-catalase interaction in model systems have been published so far [24,25]. In the work of Doronicheva et al [24] catalase activity in the presence of flavonoids has been measured using chemiluminescence method in which hypochlorous acid has been used to oxidize luminol.…”
Section: Introductionmentioning
confidence: 99%
“…These observations strongly suggest an intimate chemical interaction between OVA and rutin. Doronicheva et al demonstrated, using chemiluminescence, that the binding of flavonoids to the protein region of catalase contributed to an improvement in the activity of the enzyme (14). However, there are no reports on the alteration of the antioxidative activity of the rutin-OVA complex during the heating process.…”
Section: Resultsmentioning
confidence: 99%
“…Some paper has been reported that catelase was able to bind to catechin and had some effect on catechin activity. 41) As no effect was observed in case of C. albicans, it suggested that binding catalase to catechin had no effect on the antimicrobial activity.…”
Section: Discussionmentioning
confidence: 98%